The Aspects of Bleeding Instability of Portland Cement - Aleksei S. Brykov (Recent Progress in Science and Technology Vol. 9, 2023)
The aim of this review consists in summarizing the most recent data about cement bleeding as a colloidal chemistry phenomenon. This concept makes it possible to better understand its nature and clarify reasons for its poor predictability. Cement paste is a concentrated polydisperse suspension of cement particles in water. The particles smaller than 5-10 \(μ\)m (about 30-50%) and submicron particles (5-10%) imparts to cement paste properties of a structured (Bingham) liquid; these properties are attributed to the van der Waals forces acting between particles. Stability of cement paste against bleeding is ensured when the structure formed due to these forces is strong enough to counteract the gravity effect on even the largest particles, and to prevent their sedimentation. The intensity of bleeding of cement paste is related to the value of its yield stress in a way that when increasing the latter, the resistance to the bleeding increases. Yield stress of Portland cement paste depends on its concentration, an average size of cement particles, as well as particles’ size distribution, their shape, structure and surface nature, physical properties of the liquid and solid phases, and of many other factors. Therefore, yield stress and bleeding intensity are the properties that are difficult to predict and control.